OPTIMISATION OF WATER MANAGEMENT IN URBAN POLDERS CASE STUDIES OF THE NETHERLANDS AND THAILAND - P. Wandee; B. Schultz; T. Tingsanchali (International Association of Lowland Technology, 2006)
Rainfall in the Netherlands has moderate intensities and is more or less evenly distributed over the year while in Thailand rainfall occurs at high intensities and predominantly in the rainy season. The aim of the water management system in an urban area in a polder is to provide good drainage and discharge out of the polder. This paper presents a mathematical model for the optimisation of the main components of the water management system in urban areas in polders in the Netherlands and in Thailand. The main components of the water management system in an urban area in a polder are cross-sections of the sewers, distances between the canals, percentages of open water, canal water levels below the surface and discharge capacity of the outfall structures or the pumping stations. In order to find optional values for these main components the software package OPOL has been further developed. This package takes into account the relevant hydrological processes, construction and operation and maintenance costs for the water management system and damages due to high groundwater tables, water on the street, or even inundation under influence of rainfall and water level fluctuations in the urban canals. Optimising such a system aims at determining the main components in such a way that the annual equivalent costs will be minimal. The results of a case study for an urban polder in the area of the Principal Water-board of Delfland, the Netherlands and of another one in Bangkok, Thailand are shown. It was found that the canal water level has the largest influence on damages in these urban polders.